Gadget as Risk Factor to Speech and Language Delay in Autism Children (Department of Public Health, Faculty of Sport Science, Universitas Negeri Semarang, 2020)
Users gadgets not only among adults but the age of adolescence and early age as a kindergartner and a toddler was already using the gadget. The child’s brain at the age of 0-5 years is in the golden development period (golden age). Toddler is the most important period in optimally increasing children’s development because it can influ-ence and determine children’s development going forward. The use of gadgets from an early age will have an im-pact on children’s development that can trigger the incidence of autism. The purposed of this studied was to de-termine the effect of using gadgets on developmental delays in speech and language aspects in children with au-tism. This type of research is an observational analytic studied used a cross sectional approach. Respondents numbered 33 people. This research was conducted at the Autonomous Service UPTD of Southeast Sulawesi Edu-cation Office. Bivariate analysis showed that the intensity of the use of gadgets was related to the development of speech and language (p value = 0.011; OR = 16,000). In this case, parental supervision is very important in providing limits and controlling the playing time of the gadget to optimize the growth and development of children.